(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
This research assesses the role of climate variability in aquaculture development and its growth among stakeholders in Ghana's Upper East Region, a dry zone marked by unpredictable precipitation and growing climate instability. Conducted within the Kasena Nankana Municipal Area, the study focused on the Tono irrigation project's catchment area, which spans approximately 1,674 square kilometres, with 80 percent of the area being terrestrial. The investigation utilized descriptive and statistical methods to analyse both secondary and primary datasets. Data collection involved questionnaires, interviews, and direct observation to evaluate how climate fluctuations impact those engaged in fishing activities, with analysis performed using MS Excel and SPSS software. The sample consisted of 150 participants from the Kasena Nankana municipality, comprising 80 fishing practitioners and 70 food vendors (including fish traders, kenkey vendors, rice sellers, and fried yam vendors). Findings indicate that fishing practitioners encounter multiple interrelated challenges, with climatic conditions (identified by 42.5% of participants) and economic limitations (noted by 41.3% of participants) representing the primary concerns. These challenges are mutually reinforcing - variable climate patterns decrease fish yields, subsequently diminishing earnings and restricting capacity for equipment upgrades. The interconnected character of these challenges indicates that successful interventions require comprehensive approaches addressing multiple dimensions concurrently. Combining climate adaptation measures, economic assistance programs, and equipment modernization initiatives would prove more beneficial than tackling individual challenges separately.